Expenditure Patterns Under the Four Major Public Cash Benefit and Health Insurance Programs for Working-Age Adults With Disabilities. (September 2014) - Riley, Gerald F.; Rupp, Kalman
Using linked administrative records, we examined expenditure patterns under cash benefit and health insurance programs for 68, 794 individuals first eligible for Social Security Disability Insurance (DI) and/or Supplemental Security Income (SSI) in 2000. Expenditures were tracked until death, age 65, or December 31, 2006. Cumulative per capita expenditures averaged US$111, 160 in 2006 constant dollars, with 54% incurred under DI, 5% under SSI, and about 20% each under Medicare and Medicaid. SSI and Medicaid expenditures were somewhat higher early on. We concluded that SSI is a relatively low-expenditure program, but it has a major impact on total expenditures by providing access to Medicaid. An important role of SSI and Medicaid is to provide a temporary safety net supporting DI beneficiaries during their DI and Medicare waiting periods. The linkage of expenditure data under these four programs may be useful for evaluating the potential savings of initiatives to encourage individuals with disabilities to remain in the workforce.